Maternal sevoflurane exposure induces neurotoxicity in offspring rats via the CB1R/CDK5/p-tau pathway - Wan, Yuxiao; Wu, Ziyi; Li, Xingyue; Zhao, Ping (Frontiers in Pharmacology, 2023)
Sevoflurane is widely used for maternal anesthesia during pregnancy. Sevoflurane exposure of rats at mid-gestation can cause abnormal development of the central nervous system in their offspring. Sevoflurane is known to increase the expression of cannabinoid 1 receptor (CB1R) in the hippocampus. However, the effect of CB1R on fetal and offspring rats after maternal anesthesia is still unclear. At gestational day 14, pregnant rats were subjected to 2-h exposure to 3.5% sevoflurane or air. Rats underwent intraperitoneal injection with saline or rimonabant (1 mg/kg) 30 min prior to sevoflurane or air exposure. CB1R, cyclin-dependent kinase 5 (CDK5), p35, p25, tau, and p-tau expression in fetal brains was measured at 6, 12, and 24 h post-sevoflurane/air exposure. Neurobehavioral and Morris water maze tests were performed postnatal days 3–33. The expression of CB1R/CDK5/p-tau and histopathological staining of brain tissues in offspring rats was observed. We found that a single exposure to sevoflurane upregulated the activity of CDK5 and the level of p-tau via CB1R. This was accompanied by the diminished number of neurons and dendritic spines in hippocampal CA1 regions. Finally, these effects induced lower scores and platform crossing times in behavioral tests. The present study suggests that a single exposure to 3.5% sevoflurane of rats at mid-gestation impairs neurobehavioral abilities and cognitive memory in offspring. CB1R is a possible target for the amelioration of postnatal neurobehavioral ability and cognitive memory impairments induced by maternal anesthesia.